The morality exception in European patent law: a universal theory of interpretation devised for the Unified Patent Court - Wisniowska, Joanna (2023)
In European patent law, inventions whose commercial exploitation is contrary to morality are denied exclusive protection. This “morality patent exception” has been known for decades in European jurisdictions and international treaties, with the two most prominent examples being the EU Directive 98/44/EC on the legal protection of biotechnological inventions and the European Patent Convention (EPC). Despite its long history, to this day, no standardised interpretative rules have been agreed upon by authorities or scholars, which is a consequence of morality’s changing nature, believed impossible to form a uniform concept applicable to all jurisdictions. Lack of uniformity runs counter to harmonising agenda followed by European states. In the EPC system, the possibility of reflecting local sensibilities was preserved by a lack of procedural harmonisation at the post-grant stage, with domestic bodies responsible for patent invalidation. This situation is expected to change once the Unified Patent Court (UPC) opens its doors for litigants on 1 April 2023. European states participating in this unique project conferred on the UPC powers to hear infringement and invalidity cases concerning both the ‘bundle’ patent and the newly created European patent with unitary effect. With patent immorality no longer reviewed on a country-by-country basis, present problems are believed to escalate. In response, this research revisits legal issues surrounding the patent morality exception and proposes a novel method of its interpretation. It begins with addressing the commonly voiced convictions of morality being a term foreign to patent law, which consequently requires it to be interpreted by philosophers rather than legally qualified professionals. To prove these theories inaccurate, this research analyses a multidisciplinary meaning of morality and its relevance for patent law by applying a method of interdisciplinary transplants. In the end, an idea to perceive patent morality as a purely legal term is proposed. Based on it, the meaning of morality is sought in neighbouring areas of law, including human rights, private law, and intellectual property law. Being unable to provide a sufficiently clear and universal definition of morality, this study puts forward a novel comprehensive theory of interpretation—a functional interpretation within the systemic framework—with its two components thoroughly described and tested for the Unified Patent Court.